Permainan Ular Tangga Sebagai Media Penyuluhan Kesehatan PHBS Di SDN Muktisari 3 - Andika Abdul Malik; Nida Siti Padilah; Euis Nurmarida; Anggi Rosmawati; Sri Sulastri Desiyanti; Ganjar Triyana (Yayasan Inspirasi El Burhani, 2021)
Introduction: Childhood is often referred to as the golden period, where the growth obtained in this period greatly influences the development of the next period. Because this golden period only comes once to be used optimally. This period occurs in the middle ages of 6-12 years or commonly referred to as school age. School age is an important age in the growth and physical development of children. This period is also referred to as the critical period because at this time children begin to develop habits that tend to persist into adulthood. Objective: This study aims to determine the effectiveness of the snake and ladder game as a medium of counseling on PHBS knowledge and its application in the daily lives of students at SDN 3 Muktisari Ciamis Regency. Method: The model used for community service is health education using the concept of play. In this counseling, participants are expected to be able to implement a comprehensive (comprehensive) strategy, especially in creating new behaviors, namely PHBS in schools. Result: Based on the results of pre and post assessment of the level of knowledge, counseling participants experienced an increase. This shows that the counseling on PHBS has a positive effect for the students of SDN 3 Muktisari. In line with research (Mulyadi, 2018) that there is a significant influence before and after being given health education on the level of knowledge about clean and healthy living behavior. Conclussion: The conclusion from the implementation of this community service was counseling about PHBS using the giant snake and ladder media, giving a positive effect on the students of SD Negeri 3 Muktisari. This was shown by the enthusiasm, activeness of participants in participating in the counseling and there was also an increase in knowledge about PHBS before and after being given counseling.